ChemInform Abstract: Synthesis and Photophysical Properties of Push—Pull Structures Incorporating Diazines as Attracting Part with a Fluorene Core. Issue 6 (11th February 2014) - Denneval, Charline; Moldovan, Oana; Baudequin, Christine; Achelle, Sylvain; Baldeck, Patrice; Ple, Nelly; Darabantu, Mircea; Ramondenc, Yvan; Darabantu, Mircea; Ramondenc, Yvan
Abstract Several new push—pull fluorene derivatives such as (IV), (VI), and (VII) are prepared in order to test their photophysical properties.